2013
DOI: 10.1098/rsif.2012.0814
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of meningitis in Africa and climate forcing: aerosols stand out

Abstract: Bacterial meningitis is an ongoing threat for the population of the African Meningitis Belt, a region characterized by the highest incidence rates worldwide. The determinants of the disease dynamics are still poorly understood; nevertheless, it is often advocated that climate and mineral dust have a large impact. Over the last decade, several studies have investigated this relationship at a large scale. In this analysis, we scaled down to the district-level weekly scale (which is used for in-year response to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 69 publications
(91 reference statements)
8
100
0
2
Order By: Relevance
“…A questionable but interesting assumption is that Saharan dust may provide the bacteria N. meningitides with the iron required for growth [204,207]. Recently, Agier et al [203] found spatially consistent time-lags between seasonal components and dust events at a fine spatial scale (sanitary district); this finding, together with the assumption of dust damaging the pharyngeal mucosa and easing bacterial invasion, reinforces the notion that dust impacts meningitis' seasonality. studies have been quite well reported in recent years comparatively to climate-related studies.…”
Section: Desert Dust and Other Infectious Diseasessupporting
confidence: 61%
See 1 more Smart Citation
“…A questionable but interesting assumption is that Saharan dust may provide the bacteria N. meningitides with the iron required for growth [204,207]. Recently, Agier et al [203] found spatially consistent time-lags between seasonal components and dust events at a fine spatial scale (sanitary district); this finding, together with the assumption of dust damaging the pharyngeal mucosa and easing bacterial invasion, reinforces the notion that dust impacts meningitis' seasonality. studies have been quite well reported in recent years comparatively to climate-related studies.…”
Section: Desert Dust and Other Infectious Diseasessupporting
confidence: 61%
“…Human carriers transmit these bacteria through respiratory droplets or throat secretions. Meningitis has been associated with the dry climate conditions [196][197][198][199][200] and desert dust events [201][202][203][204][205][206]. Bacterial meningitis is an ongoing threat for the population of the African Meningitis Belt (Figure 6), a region characterized by the highest incidence rates worldwide.…”
Section: Desert Dust and Other Infectious Diseasesmentioning
confidence: 99%
“…The relationship between disease and climate apparent at large spatial scales may not be appropriate to resolve local variability, which is crucial for public health interventions in the Meningitis Belt. Within multiple districts in Niger, Agier et al (2013a) found similar time-lags between the occurrence of dust outbreaks and meningitis, which suggests that dust information may be useful in epidemiological and forecasting models. Dukić et al (2012) applied Generalized Additive Models treating time-varying confounding processes (e.g.…”
Section: The Role Of Climate and Dustmentioning
confidence: 76%
“…Epidemics and seasonal upsurges in endemic disease occur during the dry season and subside at the onset of the rains (Lapeyssonnie 1963;Molesworth et al 2002;Sultan et al 2005). The broad spatial pattern and seasonality of meningitis suggests that certain environmental factors, such as low absolute humidity (Cheesbrough et al 1995;Molesworth et al 2003) and relative humidity , temperature ) and dusty atmospheric conditions (Thomson et al 2006;Agier et al 2013a;Pérez García-Pando et al 2014) play an important role. Identifying the specific climate factor that drives epidemics is challenging because many environmental variables have a prominent seasonal cycle that covaries with disease incidence.…”
Section: The Role Of Climate and Dustmentioning
confidence: 99%
“…These environmental factors include strong northerly winds, warm temperatures, relative humidity, and aerosol loading (Sultan et al 2005;Thomson et al 2006;Yaka et al 2008;Agier et al 2013;Martgny and Chiapello 2013;Dukic et al 2013). Agier et al (2013) using satellite dust loading and assumptions as it relates to the altitude of dust loading found the highest correlations to meningitis cases with dust in the lower troposphere. Martiny and Chiapello (2013) show that positive anomalies in dust loading based on aerosol optical depth (AOD) at 440 nm, and meningitis cases in Niger and Mali are positively correlated during February through March.…”
Section: Introductionmentioning
confidence: 95%